Controlled Synthesis of NixCoyS4/rGO Composites for Constructing High-Performance Asymmetric Supercapacitor - Dong, Mingxia; Wang, Zhixing; Wang, Jiexi; Guo, Huajun; Li, Xinhai; Yan, Guochun (Frontiers in Materials, 2019)
Nickel-cobalt sulfides (NixCoyS4) are promising supercapacitor materials for their high capacitance, while the sluggish kinetics in terms of charge transfer limits their power density. To achieve both high energy and power density for the NixCoyS4 - based supercapacitor, sulfur-doped reduced graphene oxide (rGO) is incorporated into NixCoyS4 by an in situ growth – ion exchange strategy to synthesize NixCoyS4/rGO composites. Profited from the synergetic effect between rGO and NixCoyS4, the Ni1.64Co2.40S4/rGO electrode delivers high specific capacitance of 1089 F g-1 at 1 A g-1, and remains 92.6% of its capacitance at 20 A g-1 (1008 F g-1). Asymmetric supercapacitors assembled with active carbon (AC) and Ni1.64Co2.40S4/rGO (Ni1.64Co2.40S4/rGO // AC) offer both high specific capacitance (265.5 F g-1 at 1 A g-1) and superior rate capability at 50 A g-1 (recovering 63.6% of the capacitance determined at 1 A g-1). In addition, the assembled device exhibits a high capacitance retention of 92.6% after 10000 cycles at 10 A g-1, which implies an excellent cyclic stability. Ragone plot reveals that the energy density of Ni1.64Co2.40S4/rGO //AC asymmetric supercapacitor do not vanish as it delivers 30.4 Wh kg-1 at 10 kW kg-1, demonstrating its promising application.